2001
DOI: 10.1038/ncb1101-1020
|View full text |Cite
|
Sign up to set email alerts
|

A new phospholipase-C–calcium signalling pathway mediated by cyclic AMP and a Rap GTPase

Abstract: Stimulation of phosphoinositide-hydrolysing phospholipase C (PLC) generating inositol-1,4,5-trisphosphate is a major calcium signalling pathway used by a wide variety of membrane receptors, activating distinct PLC-beta or PLC-gamma isoforms. Here we report a new PLC and calcium signalling pathway that is triggered by cyclic AMP (cAMP) and mediated by a small GTPase of the Rap family. Activation of the adenylyl cyclase-coupled beta2-adrenoceptor expressed in HEK-293 cells or the endogenous receptor for prostagl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
292
6
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 303 publications
(307 citation statements)
references
References 32 publications
7
292
6
2
Order By: Relevance
“…Less extensive but consistent findings lead to a similar conclusion regarding the Rap exchange factor Epac. Despite that cAMP effectors play important roles in ␤-cell function (23,(33)(34)(35)(36), the cumulative results suggest that these cAMP effectors are not direct mediators of glucose signaling to ERK1/2 in ␤-cells.…”
Section: Discussionmentioning
confidence: 93%
“…Less extensive but consistent findings lead to a similar conclusion regarding the Rap exchange factor Epac. Despite that cAMP effectors play important roles in ␤-cell function (23,(33)(34)(35)(36), the cumulative results suggest that these cAMP effectors are not direct mediators of glucose signaling to ERK1/2 in ␤-cells.…”
Section: Discussionmentioning
confidence: 93%
“…It has been proposed that epinephrine, acting on nociceptors, produces mechanical hyperalgesia through three different signaling pathways involving 1) cAMP-dependent PKA; 2) epsilon isozyme of PKC; and 3) extracellular signal-regulated kinases 1 and 2 (1,20). It has been demonstrated that the latter two pathways may also be initiated by the accumulation of cAMP (8,35). However, recent pharmacological and electrophysiological studies have reported the presence of ␤-adrenoceptor-mediated cAMP-independent signaling pathways (38); for example, the ␤ 3 -adrenoceptor-induced relaxation of gastrointestinal smooth muscle has been proposed to be mediated through the activation of a delayed rectified K ϩ channel (15).…”
Section: Discussionmentioning
confidence: 99%
“…While the independent studies of PLCe corresponding to PLCe1a and PLCe1b demonstrated some similarities, they also pointed out potential differences in the type of agonist capable of PLCe stimulation (Evellin et al, 2002;Schmidt et al, 2001;Kelley et al, 2004). In addition, significant differences could exist regarding the ability of H-Ras to stimulate these two forms Lopez et al, 2001).…”
Section: Signaling Properties and Subcellular Localization Of Plce1a mentioning
confidence: 99%
“…In some of the studies, it was also shown that PI-PLC activity of PLCe can be stimulated by activated Ras when both molecules were introduced into COS cells Song et al, 2002). An increase in substrate hydrolysis by PLCe in transfected cells have been observed after stimulation by diverse stimuli including epidermal growth factor (EGF), lysophosphatic acid (LPA), sphingosine-1-phosphate (S1P), adrenalin and acetycholine (Schmidt et al, 2001;Evellin et al, 2002;Kelley et al, 2004). Furthermore, these and other studies suggest that signaling pathways triggered by these agonists could be quite broad and in some cases independent of Ras family GTP-ases (Lopez et al, 2001;Wing et al, 2001Wing et al, , 2003Kelley et al, 2004).…”
Section: Introductionmentioning
confidence: 99%